2011
DOI: 10.1016/j.mcn.2010.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar distribution of calcitonin gene-related peptide (CGRP) and its receptor components calcitonin receptor-like receptor (CLR) and receptor activity modifying protein 1 (RAMP1) in rat

Abstract: "Cerebellar distribution of calcitonin gene-related peptide (CGRP) and its receptor components calcitonin receptor-like receptor (CLR) and receptor activity modifying protein 1 (RAMP1) in rat."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 24 publications
5
65
0
Order By: Relevance
“…the centre of motor coordination (Gustafson et al 2005;Ross et al 1990); more interestingly, in the human cerebellum, MrgE mRNA was found in Golgi cells, which are considered inhibitory interneurons, and in Purkinje cells, which perform inhibitory motor functions (Zhang et al 2005). Recent studies in the cerebellar biology indicate that there may be a role for this organ in nociception and mechanosensation (Duggan et al 2002;Edvinsson et al 2011). Taken together, all these data demonstrate that Mrg receptors are not exclusively expressed in sensory neurons, but also in some non-sensory neurons which may be involved in mechanosensation and nociception.…”
Section: Discussionmentioning
confidence: 99%
“…the centre of motor coordination (Gustafson et al 2005;Ross et al 1990); more interestingly, in the human cerebellum, MrgE mRNA was found in Golgi cells, which are considered inhibitory interneurons, and in Purkinje cells, which perform inhibitory motor functions (Zhang et al 2005). Recent studies in the cerebellar biology indicate that there may be a role for this organ in nociception and mechanosensation (Duggan et al 2002;Edvinsson et al 2011). Taken together, all these data demonstrate that Mrg receptors are not exclusively expressed in sensory neurons, but also in some non-sensory neurons which may be involved in mechanosensation and nociception.…”
Section: Discussionmentioning
confidence: 99%
“…Direct autocrine regulation of the CGRP gene in trigeminal ganglia was demonstrated in primary cultures (39) and is supported by colocalization of CGRP and its receptor in presynaptic central terminals in situ (24, 90, 104). Investigators have also speculated that autocrine regulation of CGRP transcription occurs in the cerebellar Purkinje neurons (105). These positive feedback loops may explain why transgenic mice overexpressing the RAMP1 receptor subunit had elevated CGRP levels in cerebrospinal fluid (57).…”
Section: How Does Cgrp Contribute To Migraine?mentioning
confidence: 99%
“…Many of these areas have been implicated in migraine (Raddant and Russo, 2011). CGRP-immunopositive cell bodies and fibers are found in hypothalamic nuclei, ventral tegmental area, cerebellum, and various brainstem nuclei, including the periaqueductal grey (PAG) (Dobolyi et al, 2005; Edvinsson et al, 2011; Kresse et al, 1995; Ma et al, 2003). Furthermore, CGRP-binding sites have been localized throughout the CNS including the cortex, limbic areas (e.g.…”
Section: Calcitonin Gene-related Peptide (Cgrp)mentioning
confidence: 99%